CURBING CYBERBULLYING AMONG STUDENTS: A COMPARATIVE ANALYSIS OF EXISTING LAWS AMONG SELECTED ASEAN COUNTRIES - Ruiz, Regina Maria Niña M (PEOPLE: International Journal of Social Sciences, 2019)
Last 2013, the Philippines approved the Anti-Bullying law, which covered cyberbullying. However, a 2015 study revealed that 80% of filipino teenagers aged 13 to 16 are still experiencing cyberbullying (Takumi, 2016). This paper attempted to compare existing laws on cyberbullying among selected ASEAN (Association of Southeast Asian Nations) countries such as Indonesia, Malaysia, Philippines, Singapore, Thailand, and Vietnam. It also aims to identify each country’s anti-cyberbullying measures that might fit other ASEAN countries’ needs. To achieve its purposes, it used a qualitative research with the following primary methods: discourse analysis of cyberbullying laws and alternative strategies addressing said concern; and literature review of online journals, online publications, and online news articles. The study revealed that the Philippines is the only ASEAN country with a cyberbullying law that addresses the students, while other countries have alternative strategies in addressing the issue. Further, it found that cyberbullying is experienced by individuals aged 6 to 30 through Facebook and Twitter. The study suggests that the government should require schools to develop specific and consistent policies that would address this concern; and a curriculum that promotes digital responsibility. Finally, parents are encouraged to educate their children on ethical values, particularly in the digital world.